Dual‐mode optical thermometry and multicolor anti‐counterfeiting based on Bi3+/Er3+ co‐activated BaGd2O4 phosphor. Issue 2 (14th October 2022) - Fu, Jie; Zhou, Liuyan; Chen, Yanling; Lin, Jianhua; Ye, Renguang; Lei, Lei; Shen, Yang; Deng, Degang; Xu, Shiqing
Abstract: Here, Bi 3+, Er 3+ co‐activated gadolinium phosphors with multimode emission properties are prepared, which can emits blue, green, and orange light under the excitation of ultraviolet, 980 and 1550 nm, respectively. Moreover, BaGd2 O4 :Bi 3+, Er 3+ can show multicolor luminescence under different excitation conditions, such as pump light source, ambient temperature, working current, and other factors. Based on the dynamic luminescence characteristics, the dynamic anti‐counterfeiting experiments are designed based on the phosphor. At the same time, the material also shows multimode temperature sensing characteristics. Under the excitation of 980 nm laser, three strong up‐conversion signals Er 3+ ions are generated at 528 nm ( 2 H11/2 ), 555 nm ( 4 S3/2 ), and 668 nm ( 4 F9/2 ), which have different temperature dependences. Based on the fluorescence intensity ratio between thermal‐coupled energy levels ( 2 H11/2 / 4 S3/2 ) and nonthermal‐coupled energy levels ( 2 H11/2 / 4 F9/2 ) of Er 3+ ions, respectively, the dual‐mode temperature thermometer was constructed with high‐temperature sensitivity. In addition, the fluorescence lifetime of Bi 3+ ions also has a strong temperature dependence, which can be used as another temperature detection signal, greatly improving the stability of thermometers under harsh conditions. Therefore, the material has a bright prospect in the field of anti‐counterfeiting and temperature sensing.